The Development of Shariah Courts in The State of Yobe And Borno In Nigeria - Tijjani, Ahmed Abubakar (Al-Muqaddimah: Online Journal of Islamic History and Civilization, 2017)
Including the history of the Shariah courts in the states of Yobe and Borno, in terms of their types and degrees; the establishment of their settlement and the development that took place in the shadow of democracy; these courts are all in northern Nigeria. The establishment of Islamic courts in northern Nigeria dates back to the pre-Advent of the English, where the Borno Empire exists; in present-day Borno. This indicates that the state of Borno had an ancient civilization before the advent of the English much, and therefore the courts derive their provisions from the Islamic law and local customs in all fields of public life, including the family system, transactions, like the Islamic courts in various Islamic countries, Applied to the parents throughout the country, and this is due to historical factors, and with the development of the courts are diligent and take from the other doctrines of a sentimental clinic